2018
DOI: 10.1159/000486332
|View full text |Cite
|
Sign up to set email alerts
|

Microglial Activation Induces Generation of Oligodendrocyte Progenitor Cells from the Subventricular Zone after Focal Demyelination in the Corpus Callosum

Abstract: Neuroblasts derived from neural stem cells (NSCs) in the subventricular zone (SVZ) migrate along the rostral migratory stream into the olfactory bulb to generate interneurons under normal physiological conditions. When demyelination occurs, NSCs or neural progenitor cells (NPCs) in the SVZ provide newly formed oligodendrocytes to demyelinated lesions. The plasticity of NSC/NPC lineages may tend to oligodendrogenesis under the influence of demyelinated lesions. The mechanisms, however, still remain unknown. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…[ 64 ] Following demyelination in axons, activated microglial cells can localize at the demyelinated region and utilize neural stem and progenitor cells to produce additional OPCs from the corpus callosum's subventricular zone. [ 65 ] Of note, OPC generation is diminished when microglial activation is hindered and OPCs are killed when M1 microglia utilize TLR4 signaling pathways. [ 66 ] Thus, healing white-matter injury and initiating remyelination may benefit from employing the conversion between microglial phenotypes.…”
Section: Glial Cells and Oligodendrocytesmentioning
confidence: 99%
“…[ 64 ] Following demyelination in axons, activated microglial cells can localize at the demyelinated region and utilize neural stem and progenitor cells to produce additional OPCs from the corpus callosum's subventricular zone. [ 65 ] Of note, OPC generation is diminished when microglial activation is hindered and OPCs are killed when M1 microglia utilize TLR4 signaling pathways. [ 66 ] Thus, healing white-matter injury and initiating remyelination may benefit from employing the conversion between microglial phenotypes.…”
Section: Glial Cells and Oligodendrocytesmentioning
confidence: 99%
“…Microglial cells residing in the SVZ exhibit characteristics of an alternatively activated state, supporting adult neurogenesis, proliferation, and migration [18]. Indeed, pro-oligodendrogenic effects of microglia have been described in the early postnatal SVZ [64] and in the adult SVZ following nearby demyelination [47,65]. Selective depletion of microglia suggests that the direct contact of stem cells with microglia is not necessary for neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…79 In case of demyelination, SVZ-produced OPCs migrated to the damage area of the WM tract (including corpus callosum, fornix fimbria, and striatum) for reformation of the myelin sheath. 80 It has also been reported in mouse models that neuronal progenitor cells in SVZ generate OPCs and then continue to differentiate and grow into mature myelinated oligodendrocytes to repair the WMI. 81 Studies in vitro have confirmed the contrasting effects of Inhibin A and Matrilin 2 on OPC differentiation that makes them promising therapeutic targets for white matter recovery after ICH.…”
Section: Oligodendrogenesismentioning
confidence: 98%
“…On the theory of relevant experiments in mice with stroke, using the peroxisome proliferator‐activated receptor‐gamma agonist, rosiglitazone, can reduce the M1 phenotype microglia, increase the M2 phenotypes of microglia, induce OPC differentiation, and induce increase in the number of oligodendrocytes . In case of demyelination, SVZ‐produced OPCs migrated to the damage area of the WM tract (including corpus callosum, fornix fimbria, and striatum) for reformation of the myelin sheath . It has also been reported in mouse models that neuronal progenitor cells in SVZ generate OPCs and then continue to differentiate and grow into mature myelinated oligodendrocytes to repair the WMI .…”
Section: Repair or Recovery Mechanism And Strategymentioning
confidence: 99%